2004
DOI: 10.1016/j.cardiores.2004.01.030
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional repressor Tbx3 delineates the developing central conduction system of the heart

Abstract: We identified the T-box transcription factor Tbx3 as a novel and accurate marker for the central conduction system. Our analysis implicates a role for Tbx3 in repressing a chamber-specific program of gene expression in regions from which the components of the central conduction system are subsequently formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
176
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(184 citation statements)
references
References 41 publications
(47 reference statements)
6
176
0
2
Order By: Relevance
“…It has been shown that Tbx5 synergistically interacts with Nkx2.5 in the activation of the ANF regulatory element, responsible for expression of Anf in the cardiac chambers [9]. A similar regulatory element, composed of TBE and NKE binding sites, has been found in the promoters of other chamber-specific genes, such as Cx40 and Cx43 [10]. The lack of expression of chamber specific genes in non-chamber myocardium has been attributed to the expression of Tbx2 which is mutually exclusive with that of chamber myocardium markers [11].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been shown that Tbx5 synergistically interacts with Nkx2.5 in the activation of the ANF regulatory element, responsible for expression of Anf in the cardiac chambers [9]. A similar regulatory element, composed of TBE and NKE binding sites, has been found in the promoters of other chamber-specific genes, such as Cx40 and Cx43 [10]. The lack of expression of chamber specific genes in non-chamber myocardium has been attributed to the expression of Tbx2 which is mutually exclusive with that of chamber myocardium markers [11].…”
Section: Introductionmentioning
confidence: 93%
“…Tbx3 is co-expressed with Tbx2 in the heart in looping stages and biochemical studies suggest Tbx3, like Tbx2, is capable of repressing transcription from the ANF element in chamber specific genes [10]. In humans, haploinsufficiency of TBX3 causes the Ulnar Mammary syndrome (UMS), a pleiotropic disorder that typically presents defects in limb, mammary gland, tooth, hair and apocrine gland development [23].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of TBX3 in proximal bundle branches is associated with greater expression of connexins 40 and 43, and accordingly, faster conduction,47 which is manifest by shorter QRS duration. TBX3 deficiency can also lead to insufficient development of AVN,46 which might manifest as prolonged PR interval. Indeed, supporting this connection between QRS and PR interval, the GWAS variant associated with increased QRS interval is also associated with decreased PR interval 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple transcriptional repressors have been show to influence formation and function of the conduction system. For example, Tbx2 and Tbx3 are expressed within the central conduction system to repress working cardiomyocyte-specific genes (11,12). To accomplish this function, they interact with Nkx2.5 and prevent transcriptional activation of the chamber-specific genes Nppa and Cx43 to reinforce conduction cell identity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while Tbx5 and Nkx2.5 are expressed broadly within the developing heart to activate transcription, the inhibitory T-box transcription factors Tbx2 and Tbx3 are confined to AV node progenitor cells and repress working cardiomyocyte-specific genes (i.e., Nppa and Cx43) by antagonizing Nkx2.5 (11)(12)(13)(14)(15). In addition, well-characterized signaling pathways influence these transcriptional mechanisms to refine AVN morphogenesis.…”
mentioning
confidence: 99%